Regional Economic Outlook, April 2011, Middle East and Central Asia. (Regional Economic Outlook, 2011)
This issue of the Regional Economic Outlook: Middle East and Central Asia provides an in-depth look at the Middle East, North Africa, Afghanistan, and Pakistan (MENAP) region, as well as the Caucasus and Central Asia (CCA). Four chapters deal with MENAP oil exporters, MENAP oil importers, policy challenges facing MENAP, and sustaining the recovery in the CCA countries. Two developments mark the outlook for the MENAP region: the social and political unrest and the surge in global fuel and food prices, which have resulted in unusually large uncertainties in the near-term economic outlook. Meanwhile, growth in the CCA countries was higher than expected. Three main policy challenges to CCA countries are rising inflation, heightened social pressures to spend, and the poor quality of bank portfolios. Job creation and poverty reduction are key objectives for all CCA countries.